Pengaruh Eefktivitas Sistem Pemungutan PPN Dan Pengawasan Sistem Pemungutan PPN Terhadap Kepatuhan Wajib Pajak Pengusaha Vape (Studi Kasus Rokok Elektrik Pada Pengusaha Vape Yang Bergabung Dengan APVI di Indonesia Tahun 2019 - Feren Kafitri Fardi; Daryanto Hesti Wibowo (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study discusses the influence of the effectiveness of the VAT collection system and the supervision of the VAT collection system on the compliance of vape entrepreneur taxpayers. This a case study of ecigarettes on vape entrepreneurs who were members of APVI (Association of Personal Vaporizer in Indonesia) in 2019. The purpose of this study was to analyze the influence of the effectiveness of the VAT collection system and the supervision of the VAT collection system on the compliance of vape entrepreneur taxpayers. This research was conducted using a quantitative approach. The population was taxpayers who were members of APVI in 2019. The sample consisted of 116 respondents who were determined using the Slovin formula. The data analysis methods used included instrument tests consisting of validity tests, reliability tests, and descriptive statistics; assumption test; and statistical analysis consisting of multiple linear regression analysis, t test, F test, correlation coefficient and coefficient of determination (R2) carried out using the SPSS 26 application for windows. Based on the results of the study, it was found that the effectiveness of the VAT collection system has a significant influence with a tcount of 26.805 and the supervision of the VAT collection system has a significant influence with a tcount 19.323. The results of the simultaneous test (F test) show an Fcount value of 406.697 with a significance value (0.000 <0.05), so the hypothesis that the effectiveness of the VAT collection system and the supervision of the VAT collection system influence vape entrepreneur taxpayer compliance is accepted. Simultaneously these two variables have an influence of 87.8%.